DEVELOPED MUSIC TEACHING KIT OF PAKEM FOR ELEMENTARY SCHOOL MUSIC LEARNING - Yermiandhoko, Yoyok (Harmonia: Journal of Arts Research and Education, 2014)
The objective of the research was to: (1) construct a model and develop a music teaching kit of PAKEM which were appropriately applied to the music teaching learning process in the third grade of elementary schools; (2) describe the level of conceptual feasibility; (3) describe the level of operational feasibility; and (4) describe the level of effectiveness of the music teaching kit of PAKEM developed. This research uses eight steps of development which is the modification of 10 steps of Borg Galldevelopment research. The data to be analyzed included (1) the observation data of teachers and students; (2) the survey form for teachers and students; (3) the students’ learning result of music class; and (4) the result of students’ performance of musical ability. The results of development research indicated that the music teaching kit developed: (1) can be used by teachers without encountering difficulties; (2) can last eliminating difficulties and limitations in conducting music teacher learning process; (3) is able to engage students actively; (4) is capable of motivating students to enjoy learning music; and (5) is able to improve the results of music learning in theory and practice.